Strong convergence of a general iterative algorithm for asymptotically nonexpansive semigroups in Banach spaces - Liu, Lishan; Liu, C.; Wang, F.; Wu, Yong Hong (Shomal University, 2016)
© 2016 All rights reserved.In this paper, we study a general iterative process strongly converging to a common fixed point of an asymptotically nonexpansive semigroup {T(t): t ? R+} in the framework of re exive and strictly convex spaces with a uniformly Gáteaux differentiable norm. The process also solves some variational inequalities. Our results generalize and extend many existing results in the research field.